2020
DOI: 10.3390/toxins12010033
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Limitation Increases Content of Protease Inhibitors in the Cyanobacterium Microcystis aeruginosa

Abstract: Increased anthropogenic nutrient input has led to eutrophication of lakes and ponds, resulting worldwide in more frequent and severe cyanobacterial blooms. In particular, enhanced availability of phosphorus (P) can promote cyanobacterial mass developments and may affect the content of secondary metabolites in cyanobacteria, such as protease inhibitors (PIs). PIs are common among cyanobacteria and have been shown to negatively affect herbivorous zooplankton. Here, we test the hypothesis that P-limitation reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…These data match the result of Teikari and colleagues [ 94 ], who studied the same Anabaena strain and encountered higher quantities of transcripts belonged to anabaenopeptins, anabaenopeptilide, and microcystins gene clusters under low-phosphate conditions. Phosphate limitation also increases the content of protease inhibitors of the cyanobacterium M. aeruginosa NIVA CYA 43 [ 95 ].…”
Section: Occurrence Of Anabaenopeptins and Factors Involved In Their Expressionmentioning
confidence: 99%
“…These data match the result of Teikari and colleagues [ 94 ], who studied the same Anabaena strain and encountered higher quantities of transcripts belonged to anabaenopeptins, anabaenopeptilide, and microcystins gene clusters under low-phosphate conditions. Phosphate limitation also increases the content of protease inhibitors of the cyanobacterium M. aeruginosa NIVA CYA 43 [ 95 ].…”
Section: Occurrence Of Anabaenopeptins and Factors Involved In Their Expressionmentioning
confidence: 99%
“…In this context, it has to be noted that the protease inhibitor content of a cyanobacterial strain may vary. As shown for strain NIVA Cya 43 (Burberg et al 2019, 2020), Schwarzenberger et al (2013 b ) demonstrated that the protease inhibitor content of M. aeruginosa strain BM25 was strongly affected by available nutrient ratios. In accordance with the carbon‐nutrient‐balance hypothesis (van de Waal et al 2014) the content of the N‐containing protease inhibitors in BM25 decreased under N‐limitation (C : N = 13) and increased under P‐limitation (C : P = 234).…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, phosphates were sufficient for supporting cyanobacteria growth, even at the lowest concentrations measured (Table 1). High phosphate loads definitely promote the cyanobacterial biomass accumulation (Burberg et al, 2020), as indicated in the context of eutrophication. This phenomenon is often attributed to the high content of phosphates in cleaning agents and fertilizers, and even the influence of climate change can promote phosphates accumulation in waterbodies (Forber et al, 2018;Wilson et al, 2019).…”
Section: Discussionmentioning
confidence: 95%